Funding sources for public health research in Italy - Mazzoli, Riccardo; La Torre, Maria; Privitera, Vanessa E.; Sändig, Nadja; Filippini, Tommaso; Vinceti, Marco (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Funding sources play a critical role in shaping the landscape of scientific research, including the one in public health, as they often determine not only the feasibility of specific projects but also its broader directions. Study design. We aimed at assessing current funding sources for public health research in Italy and related implications. Methods. We conducted a systematic PubMed search from January 2023 to June 2024, focusing on publications by 208 Italian tenured professors in hygiene and public health. We included only original articles they authored as first or last authors, excluding editorials, comments, and letters. We categorized funding sources into public internal, public external, private external, and unmentioned. Results. We retrieved 760 non-duplicate eligible publications. Research topics focused almost equally on communicable (48.2%) and non-communicable (51.8%) diseases. Public external funding were the most common overall (33.7%), followed by private external (14.3%) and public internal (7.5%). Notably, 58.7% of studies did not report any funding sources. Private external, regional and EU sources predominantly funded communicable disease research, while non-communicable disease research received more support from public external sources, especially governmental. Conclusions. In a European country such as Italy the funding landscape in public health research appears to be complex, due to the wide range of topics and intertwined roles of funding actors. Public funding are more frequent than private funding also independently of research topics, though most research activities did not require specific financial support, implying that public health research frequently has limited financial needs. This likely enables more flexibility and independence to investigators in public health, with major implications in terms of feasibility and absence of conflicts of interest.